PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS HIGHER ORDER THINKING SKILL (HOTS) PADA MATERI GETARAN, GELOMBANG DAN BUNYI - Antis Ineswati Puspitasari; Aris Singgih Budiarso; Pramudya Dwi Aristya Putra (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
The Higher Order Thinking Skills of students is still very weak. This is due to the lack of teaching materials that can be used to train higher thinking skills. The way to improve students' HOTS skills is to develop student worksheets. Student Worksheets (LKPD) are tools that facilitate student learning and lead to effective interactions between students and teachers. The purpose of this study was to determine the validity, practicality and effectiveness of HOTS-based LKS development. The type of research used is the ADDIE model development research which has stages of analysis, design, development, implementation and evaluation. The HOTS-based LKPD validation results for vibration, wave and acoustic materials using the validation form reach an average percentage of six aspects or 92%, meaning that the conformity between the products produced and the LKPD production criteria is valid. The results of the HOTS-based LKPD practicum with vibration, wave and sound material using practicum study sheets reached an average of 89.44 and the category was very practical to use in the learning process. The results of the effectiveness of the HOTS-based LKPD for vibration, wave and sound material using the N-Gain value in the pre and post test of 0.55 are in the medium category, so that students' higher order thinking skills increase after using LKPD. Increase in HOTS-based LKPD during this period. The effectiveness of the product being developed was also determined by a survey of student responses consisting of interest, material and language reaching 95.17%, which means a very good category.